THE EFFECT OF BABY SPA (BABY MASSAGE, BABY SWIM, AND BABY GYM) ON THE QUALITY OF SLEEP AND GROWTH OF BABIES AGED 0-6 MONTHS - Hendriyani, Feftin (Global Ten Public Health and Nursing Journal, 2023)
Abstract Background: The most rapid development of babies occurs during the golden age so stimulation becomes very important in the process of growth and development. At this time, if stimulation factors are not provided enough, the child will experience problems with sleep quality and growth, such as weight gain and gross motor skills. This research aims to explain the effect of baby SPA (baby massage, baby swim, and baby gym) on sleep quality and growth and development (weight and gross motor skills) of babies aged 0-6 months. Method: A literature review was carried out through searching for relevant articles from electronic databases (Scient Direction, Pubmed, Google Scholar,) using the following keywords: "baby SPA", "baby massage", "baby swim", "baby gym", " baby weight”, “Sleeping baby”, “gross motor”, “baby”, “0-6 months”, “baby”, “baby massage”, “baby gymnastics”, “baby swimming”. There were 15 articles obtained from 2017 – 2021 and an in-depth analysis was carried out. Research results: show that there is an influence of baby SPA (baby massage, baby swim, and baby gym) on sleep quality, body weight, and gross motor skills of babies aged 0-6 months. Conclusion: The importance of providing baby SPA (baby massage, baby swim, and baby gym) on sleep quality, body weight, and gross motor skills of babies aged 0-6 months so that babies get optimal growth and development during their golden ages. Keywords: Baby SPA, baby massage, baby swim, baby gym, sleeping baby, baby weight, gross motor skills.